Long-term basketball training shapes cerebellar-frontal integration for enhanced cognitive control - Fang, W.; Qi, Y.; Wang, Y.; Li, K.; Du, X.; Shao, B. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background In competitive sports, elite athletes demonstrate exceptional proficiency in resolving sensorimotor conflicts, exemplified by the basketball head-fake phenomenon. Whether long-term basketball training leads to adaptive cognitive control in athletes and the underlying neural mechanisms is still unclear.